Nutritional status in patients with rheumatoid arthritis: is there an association with the sarcopenic phenotype of body composition? - O. V. Dobrovolskaya; N. V. Demin; O. A. Nikitinskaya; N. V. Toroptsova; A. Yu. Feklistov (Научно-практическая ревматология)
Aim – to evaluate the nutritional status and its relationship with the sarcopenic phenotype of body composition in women with rheumatoid arthritis (RA).Material and methods. The study included 91 women aged 40 to 75 years with RA according to ACR/EULAR criteria (2010) and a disease duration of at least 1 year. A questionnaire, laboratory and densitometric examination were conducted. Nutritional status was assessed using a MNA (Mini Nutricial Assessment) questionnaire.Results. Malnutrition and at risk of malnutrition according to the MNA were detected in 44.0% of patients with RA. These patients differed from those with normal nutritional status with a higher risk of osteoporotic hip fractures according to FRAX (p=0.035), lower appendicular muscle mass (AMM) (p=0.048) and lower self-assessment of health status (p=0.012). Patients significantly differed in nutritional status according to MNA, daily intake of calcium with food, circumferences of the mid-upper arm, calf, waist and hips, depending on the presence of sarcopenic phenotype. Multivariate regression analysis showed that the sarcopenic phenotype was associated with a nutritional status according to MNA less than 24 points (odds ratio (OR) – 6.14; p=0.036), daily calcium intake less than 500 mg (OR=9.55; p=0.007) and mid-upper arm circumference less than 25 cm (OR=9.32; p=0.015).Conclusion. Malnutrition was found in almost half of the patients with RA. It was revealed that a low nutritional status according to the MNA, low calcium intake and mid-upper arm circumference less than 25 cm increased the risk of having a sarcopenic phenotype in women with RA.